2020
DOI: 10.3390/biom10020283
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonoylcholine and Other Unsaturated Long-Chain Acylcholines Are Endogenous Modulators of the Acetylcholine Signaling System

Abstract: Cholines acylated with unsaturated fatty acids are a recently discovered family of endogenous lipids. However, the data on the biological activity of acylcholines remain very limited. We hypothesized that acylcholines containing residues of arachidonic (AA-CHOL), oleic (Ol-CHOL), linoleic (Ln-CHOL), and docosahexaenoic (DHA-CHOL) acids act as modulators of the acetylcholine signaling system. In the radioligand binding assay, acylcholines showed inhibition in the micromolar range of both α7 neuronal nAChR overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Long-chain acylcholines have been found to have associations with a number of disease states (115), including elevated concentrations in endometrial cancer patients (116) and patients at high risk of pulmonary embolism (117), and lower concentrations in patients with myalgic encephalomyelitis/chronic fatigue syndrome (118) and chronic thromboembolic pulmonary hypertension (119). Acylcholines are known to have cholinergic signaling properties, with important implications for signaling through the nicotinic acetylcholine receptor (α7 nAChR), and effects on cytokine synthesis in macrophages and T cells (115,120).…”
Section: Discussionmentioning
confidence: 99%
“…Long-chain acylcholines have been found to have associations with a number of disease states (115), including elevated concentrations in endometrial cancer patients (116) and patients at high risk of pulmonary embolism (117), and lower concentrations in patients with myalgic encephalomyelitis/chronic fatigue syndrome (118) and chronic thromboembolic pulmonary hypertension (119). Acylcholines are known to have cholinergic signaling properties, with important implications for signaling through the nicotinic acetylcholine receptor (α7 nAChR), and effects on cytokine synthesis in macrophages and T cells (115,120).…”
Section: Discussionmentioning
confidence: 99%
“…Our unpublished data allow suggesting that phosphocholine also affects α7 nAChRs. Recently published evidence demonstrates that long-chain unsaturated acylcholines can be viewed as endogenous modulators of α7 nAChRs (Akimov et al, 2020) These choline derivatives are natural components of membrane lipids, which, similarly to α7 nAChRs agonists, can affect SVs fusion with the PM and the process of neurotransmitter release. In contrast to fusion, which was affected similarly by nicotine and PNU282987 activating both α4β2 and α7(β2) nAChRs, SVs acidification was affected by nicotine only suggesting that α7 nAChRs are not involved in regulating the proton flux (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Figure 2C displays that solubilized chrysin-NE inhibited BChE more than pure chrysin. It could be possible that medium chain fatty acids and chrysin may have a combined inhibitory effect on BChE [33]. Data showed that chrysin exhibited biological activities in vitro, even after nanoemulsion development.…”
Section: Effects Of Nanoemulsion Preparation On Chrysin Biological Activitiesmentioning
confidence: 99%